Accuracy of CCL20 expression level as a liquid biopsy-based diagnostic biomarker for ovarian carcinoma - Sakares, Watchara; Wongkhattiya, Wannaporn; Vichayachaipat, Ponlawat; Chaiwut, Chompunoot; Yodsurang, Varalee; Nutthachote, Pattiya (Frontiers in Oncology, 2022)
Objective The study aimed to investigate the potentiality of chemokines, including MCP-1, CCL15, CCL20, and CXCL14, as biomarkers for differential diagnosis between benign tumors and ovarian cancer (OC). Methods A cross-sectional study was conducted in women aged >18 years who had adnexal masses treated with elective surgery at the HRH Maha Chakri Sirindhorn Medical Center, Srinakharinwirot University, between 2020 and 2021. The preoperative MCP-1, CCL15, CCL20, and CXCL14 serum levels were measured using a sandwich enzyme-linked immunosorbent assay. Preoperative diagnosis was defined according to the risk of malignancy index. The histological diagnosis and cancer subtype were confirmed using pathological specimens. Results Ninety-eight participants were preoperatively diagnosed with malignant tumors. The pathological diagnosis confirmed OC in 33 patients and disclosed 27 misdiagnosed cases, of which endometriotic cyst was the most common (44.44%). CCL20 and CA125 serum levels were significantly higher in the patients with cancer than in those with benign. In addition, CCL20 level could differentiate between benign and early-stage malignancy. Furthermore, only CCL20 levels could distinguish endometriotic cysts from OC, whereas CA125 levels could not. Concordant with the serum protein level, the increased mRNA level of CCL20 was observed in ovarian cancers comparing with that in benign tissues. We found that CCL20 levels could differentiate between benign tumors and OC with 60.61% sensitivity and 75.44% specificity at the optimal cutoff value of 38.79 pg/ml. Finally, the logistic regression model integrating CCL20, CA125, and menopause status promoted diagnostic accuracy by increasing the specificity to 91.23%. Conclusions Our study revealed the potential usefulness of CCL20 level as a biomarker for diagnosing early-stage OC with endometriosis differentiation. We recommend further studies to confirm the accuracy of CCL20 levels with the current diagnosis in a large patient sample.